Diaphragm, preparation method thereof and secondary battery
By using acrylamide copolymer separators with self-regulating thermal shutdown effect in lithium-ion batteries, the problem of thermal runaway in lithium-ion batteries is solved, improving the safety performance of the battery and maintaining the electrochemical performance.
Patent Information
- Application Number
- CN202311057172.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-21
AI Technical Summary
Existing lithium-ion batteries are prone to thermal runaway at high temperatures, resulting in battery capacity attenuation and safety hazards. Existing solutions such as adding flame retardant substances or using fire extinguishing agents have deterioration or irreversibility problems.
A separator containing an acrylamide copolymer is used which is hydrophilic at ambient temperature below its minimum co-soluble temperature, allowing lithium ions to conduct; and converts to hydrophobic at a temperature above its minimum co-soluble temperature. , close the lithium ion channel to achieve self-regulated thermal shutdown effect.
Without affecting the electrochemical performance, the diaphragm effectively avoids the thermal runaway problem of lithium-ion batteries, improves the overall safety performance of the battery, and realizes reversible regulation of lithium-ion channels.
Smart Images

Figure CN119495907A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a secondary battery, and specifically provides a diaphragm and a preparation method thereof, and a secondary battery. Background Art
[0002] With the development of the new energy vehicle industry, secondary batteries are expected to have higher energy density. However, high energy density secondary batteries such as lithium batteries are often accompanied by safety hazards that are difficult to ignore. This is because most current lithium-ion batteries use organic liquid electrolytes. The loss of active substances and the side reactions of the electrolyte at high temperatures not only cause the rapid decay of the battery capacity, but also may cause the battery to spontaneously combust or even explode if the heat continues to accumulate. Some traditional methods for solving thermal runaway include adding flame retardants to the electrolyte, or using disposable fire extinguishing agents to cut off the current collector, etc., but the former will degrade the electrochemical properties of the battery (such as cycle performance), and the latter is an irreversible means. Once activated, the battery cannot be used subsequently.
[0003] Therefore, there is an urgent need in the art for a secondary battery that can avoid thermal runaway as much as possible. Summary of the invention
[0004] In order to solve the above problems, the purpose of the present invention is to provide a diaphragm, which has good lithium ion conductivity and will not have a negative impact on the electrochemical performance of the battery while maintaining a sensitive thermal shutdown effect and improving the overall safety performance of the battery.
[0005] The object of the present invention is to provide a diaphragm, which comprises: a base film; a copolymer layer, wherein the copolymer layer is disposed on the base film, the copolymer layer comprises an acrylamide copolymer, and the acrylamide copolymer comprises a first unit as shown in formula I and a second unit as shown in formula II:
[0006]
[0007] Wherein, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 16% to 96%, and the mass percentage of the second unit is 4% to 84%.
[0008] The present invention also aims to provide a method for preparing a diaphragm, comprising:
[0009] Mixing acrylamide monomer, N-isopropylacrylamide monomer, crosslinking agent, catalyst and solvent to obtain a first mixture;
[0010] adding an initiator to the first mixture, and obtaining a second mixture containing an acrylamide copolymer through reaction treatment;
[0011] The second mixture is coated on a base film, and the separator is obtained through a drying process.
[0012] The present invention also aims to provide a secondary battery, which comprises a positive electrode sheet, a negative electrode sheet, an electrolyte, and a diaphragm according to the present application or a diaphragm prepared according to the method of the present application.
[0013] The beneficial effects of this application are:
[0014] The lower critical solution temperature (LCST) of the acrylamide copolymer in the diaphragm is its own property. When the temperature of the environment in which the acrylamide copolymer is located (for example, the diaphragm is located in the electrolyte, corresponding to the temperature of the electrolyte) is lower than its LCST, the acrylamide copolymer is hydrophilic (for example, a hydrophilic hydrogel), and the electrolyte swells, and the lithium ions in the electrolyte can be freely transmitted through the diaphragm, and the secondary battery can work normally; when the temperature of the environment in which the acrylamide copolymer is located is higher than its LCST (for example, the temperature of the electrolyte rises), the acrylamide copolymer can be converted into a hydrophobic material, and then the electrolyte is discharged, the lithium ion channel is closed, the reaction of the positive and negative electrodes is cut off, and the heat of the secondary battery is prevented from further accumulating, that is, the diaphragm realizes a self-regulating thermal shutdown effect. Moreover, the hydrophilicity or hydrophobicity of the acrylamide copolymer is completely reversible at an ambient temperature lower than or higher than its LCST. Therefore, when the diaphragm using the acrylamide copolymer is used in a secondary battery, on the one hand, it can achieve a thermal shutdown effect at high temperature. On the other hand, if the ambient temperature of the acrylamide copolymer drops below its LCST, the lithium ion channel is restored and the secondary battery can still be used normally. Based on the above improvements, the present invention obtains a diaphragm with high lithium ion conductivity and self-regulating thermal shutdown effect by arranging the acrylamide copolymer on the diaphragm to form a copolymer layer, thereby solving the thermal runaway problem of the secondary battery and improving the safety performance of the secondary battery without affecting the electrochemical performance. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described in conjunction with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. The relevant embodiments described herein are illustrative and are used to provide a basic understanding of the present invention. The embodiments of the present invention should not be interpreted as limiting the present invention. All other embodiments obtained by those skilled in the art based on the technical scheme provided by the present invention and the embodiments given belong to the scope of protection of the present invention.
[0016] Unless otherwise specified, the terms used in the present invention have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in the present invention can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of the present invention).
[0017] A list of items connected by the terms "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0018] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0019] Diaphragm
[0020] The object of the present invention is to provide a diaphragm, which comprises: a base film and a copolymer layer, wherein the copolymer layer is arranged on the base film, the copolymer layer comprises an acrylamide copolymer, and the acrylamide copolymer comprises a first unit as shown in formula I and a second unit as shown in formula II:
[0021]
[0022] Wherein, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 16% to 96%, and the mass percentage of the second unit is 4% to 84%. It should be noted that in Formula I and Formula II, "*" represents a connection site for connecting with other structures or groups.
[0023] The lower critical solution temperature (LCST) of the acrylamide copolymer in the diaphragm is its own property. When the temperature of the environment in which the acrylamide copolymer is located (for example, the diaphragm is located in the electrolyte, corresponding to the temperature of the electrolyte) is lower than its LCST, the acrylamide copolymer is hydrophilic (for example, a hydrophilic hydrogel), and the electrolyte swells, and the lithium ions in the electrolyte can be freely transmitted through the diaphragm, and the secondary battery can work normally; when the temperature of the environment in which the acrylamide copolymer is located is higher than its LCST (for example, the temperature of the electrolyte rises), the acrylamide copolymer can be converted into a hydrophobic material, and then the electrolyte is discharged, the lithium ion channel is closed, the reaction of the positive and negative electrodes is cut off, and the heat of the secondary battery is prevented from further accumulating, that is, the diaphragm realizes a self-regulating thermal shutdown effect. Moreover, the hydrophilicity or hydrophobicity of the acrylamide copolymer is completely reversible at an ambient temperature lower than or higher than its LCST. Therefore, when the diaphragm using the acrylamide copolymer is used in a secondary battery, on the one hand, it can achieve a thermal shutdown effect at high temperature. On the other hand, if the ambient temperature of the acrylamide copolymer drops below its LCST, the lithium ion channel is restored and the secondary battery can still be used normally. Based on the above improvements, the present invention obtains a diaphragm with high lithium ion conductivity and self-regulating thermal shutdown effect by arranging the acrylamide copolymer on the diaphragm to form a copolymer layer, thereby solving the thermal runaway problem of the secondary battery and improving the safety performance of the secondary battery without affecting the electrochemical performance.
[0024] According to some embodiments of the present invention, the acrylamide copolymer includes: a copolymer obtained by copolymerization of acrylamide monomer and N-isopropylacrylamide monomer. According to some embodiments of the present invention, the acrylamide copolymer consists of a copolymer obtained by copolymerization of acrylamide monomer and N-isopropylacrylamide monomer. According to some embodiments of the present invention, in the acrylamide copolymer, the arrangement of the first unit and the second unit includes at least one of random copolymerization, alternating copolymerization, block copolymerization and graft copolymerization. It should be noted that the first unit may be derived from an acrylamide monomer, and the second unit may be derived from an N-isopropylacrylamide monomer. The acrylamide copolymer formed by the random copolymerization of the first unit and the second unit may be a random copolymer, in which different types of structural units are randomly arranged, for example, the distribution of the first unit and the second unit is random. The acrylamide copolymer formed by the alternating copolymerization of the first unit and the second unit can be an alternating copolymer, in which the first unit and the second unit appear alternately, for example, the first unit and the second unit are alternately arranged along the alternating copolymer chain. Further, if there are only two different types of structural units, "A" and "B", the alternating copolymer will be "...ABABABAB...", if there are three different types of structural units, "A", "B" and "C", the alternating copolymer will be "...ABCABCABC...". The acrylamide copolymer formed by the block copolymerization of the first unit and the second unit can be a block copolymer (or mosaic copolymer). In the block copolymer, there are different blocks, each block is formed by one type of structural unit, and the block copolymer can be described by the order of the blocks. For example, if one type of block is formed by the structural unit "A", and the other type of block is formed by the monomer "B", its block copolymer can be described by the general formula...-A k -B l -A m -B n -...to describe; k, l, m and n represent the number of structural units in each block. More specifically, the block copolymer comprises: a first segment containing a longer structure (e.g., hundreds to thousands of first units) and another second segment containing a longer structure (e.g., hundreds to thousands of second units). The acrylamide copolymer formed by the graft copolymerization of the first unit and the second unit can be a graft copolymer (or branched polymer). In the graft copolymer, there are side chains along its main chain. The side chains and the main chain can be chemically the same or different from each other. For example, the main chain contains the first unit (or consists of one or more first units), and the side chain contains the second unit (or consists of one or more second units), or the main chain contains the second unit (or consists of one or more second units), and the side chain contains the first unit (or consists of one or more first units).
[0025] According to some embodiments of the present invention, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 16% to 96%, and the mass percentage of the second unit is 4% to 84%. Specifically, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 16%, 18%, 20%, 25%, 28%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 92%, 94%, 96% or any value therebetween, and the mass percentage of the second unit is 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 25%, 28%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 72%, 75%, 80%, 84% or any value therebetween. According to some embodiments of the present invention, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 28% to 94%, and the mass percentage of the second unit is 6% to 72%. According to some embodiments of the present invention, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 40% to 80%, and the mass percentage of the second unit is 20% to 60%. According to some embodiments of the present invention, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 30% to 70%, and the mass percentage of the second unit is 30% to 70%. According to some embodiments of the present invention, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 40% to 60%, and the mass percentage of the second unit is 40% to 60%.
[0026] According to some embodiments of the present invention, the weight average molecular weight of the acrylamide copolymer is 200,000 Da to 2,000,000 Da. Specifically, the weight average molecular weight of the acrylamide copolymer is 200,000 Da, 300,000 Da, 400,000 Da, 500,000 Da, 600,000 Da, 700,000 Da, 800,000 Da, 1,000,000 Da, 1,200,000 Da, 1,400,000 Da, 1,600,000 Da, 1,800,000 Da, 2,000,000 Da or any value therebetween. According to some embodiments of the present invention, the weight average molecular weight of the acrylamide copolymer is 300,000 Da to 800,000 Da. According to some embodiments of the present invention, the weight average molecular weight of the acrylamide copolymer is 400,000 Da to 500,000 Da.
[0027] According to some embodiments of the present invention, the base film includes at least one of polyethylene, polypropylene, polypropylene / polyethylene / polypropylene three-layer film (PP / PE / PP), polyethylene terephthalate, polyimide and aramid. The thickness of the base film is 2 μm to 12 μm. Specifically, the thickness of the base film is 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or any value therebetween.
[0028] According to some embodiments of the present invention, the copolymer layer is disposed on surfaces of opposite sides of the base film.
[0029] According to some embodiments of the present invention, the thickness of the copolymer layer is 1 μm to 10 μm. Specifically, the thickness of the copolymer layer is 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or any value therebetween. According to some embodiments of the present invention, the thickness of the copolymer layer is 2 μm to 5 μm.
[0030] According to some embodiments of the present invention, the minimum solubility temperature of the acrylamide copolymer is 50°C to 110°C. Specifically, the minimum solubility temperature of the acrylamide copolymer is 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C or any value therebetween. According to some embodiments of the present invention, the minimum solubility temperature of the acrylamide copolymer in the diaphragm is 55°C to 85°C. According to some embodiments of the present invention, the minimum solubility temperature of the acrylamide copolymer in the diaphragm is 55°C to 70°C. The ambient temperature of the acrylamide copolymer is greater than the minimum solubility temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 100° to 170°, specifically, the contact angle of the acrylamide copolymer is 100°, 110°, 120°, 130°, 140°, 150°, 160°, 170° or any value therebetween. The temperature of the environment in which the acrylamide copolymer is located is lower than the minimum solubility temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 20° to 70°. Specifically, the contact angle of the acrylamide copolymer is 20°, 30°, 40°, 50°, 60°, 70° or any value therebetween.
[0031] It should be noted that the Lower Critical Solution Temperature (LCST) of the acrylamide copolymer in the diaphragm is its own property. When the ambient temperature of the acrylamide copolymer (for example, the diaphragm is in the electrolyte, corresponding to the temperature of the electrolyte) is lower than its LCST, the acrylamide copolymer is hydrophilic (for example, a hydrophilic hydrogel), and the electrolyte swells, and the lithium ions in the electrolyte can be freely transmitted through the diaphragm, and the secondary battery can work normally; when the ambient temperature of the acrylamide copolymer is higher than its LCST (for example, the temperature of the electrolyte rises), the acrylamide copolymer can be converted into a hydrophobic material, and then the electrolyte is discharged, closing the lithium ion channel, cutting off the reaction of the positive and negative electrodes, and preventing the further accumulation of heat in the secondary battery, that is, the diaphragm realizes a self-regulating thermal shutdown effect. Moreover, the hydrophilicity or hydrophobicity of the acrylamide copolymer is completely reversible at an ambient temperature lower than or higher than its LCST. Therefore, when the diaphragm using the acrylamide copolymer is used in a secondary battery, on the one hand, it can achieve a thermal shutdown effect at high temperature. On the other hand, if the ambient temperature of the acrylamide copolymer drops below its LCST, the lithium ion channel is restored and the secondary battery can still be used normally. Based on the above improvements, the present invention obtains a diaphragm with high lithium ion conductivity and self-regulating thermal shutdown effect by arranging the acrylamide copolymer on the diaphragm to form a copolymer layer, thereby solving the thermal runaway problem of the secondary battery and improving the safety performance of the secondary battery without affecting the electrochemical performance. For example, when the minimum eutectic temperature of the acrylamide copolymer is 65°C, and the ambient temperature of the acrylamide copolymer is lower than 65°C, the acrylamide copolymer is hydrophilic, and the electrolyte swells, and the lithium ions in the electrolyte can be freely transmitted through the diaphragm, and the secondary battery can work normally; when the ambient temperature of the acrylamide copolymer is higher than 65°C, the acrylamide copolymer can be converted into a hydrophobic material, and then the electrolyte is discharged, the lithium ion channel is closed, the reaction of the positive and negative electrodes is cut off, and the heat of the secondary battery is prevented from further accumulating, that is, the diaphragm realizes a self-regulating thermal shutdown effect.
[0032] Preparation method of diaphragm
[0033] The present invention also aims to provide a method for preparing a diaphragm, wherein the diaphragm prepared by the method may be the diaphragm described above, thereby having all the characteristics and advantages of the diaphragm described above. The method comprises:
[0034] S100: mixing acrylamide monomer, N-isopropylacrylamide monomer, a cross-linking agent, a catalyst and a solvent to obtain a first mixture;
[0035] S200: adding an initiator to the first mixture, and obtaining a second mixture containing an acrylamide copolymer through reaction treatment;
[0036] S300: coating the second mixture on a base film, and obtaining the separator through a drying process.
[0037] The minimum solubility temperature (LCST) of the acrylamide copolymer according to the present invention can be regulated by controlling the ratio of the acrylamide monomer and the N-isopropylacrylamide monomer. When the temperature of the environment in which the acrylamide copolymer is located (for example, the diaphragm is located in the electrolyte, corresponding to the temperature of the electrolyte) is lower than its LCST, the acrylamide copolymer is hydrophilic (for example, a hydrophilic hydrogel), and for the swelling of the electrolyte, the lithium ions in the electrolyte can be freely transmitted through the diaphragm, and the secondary battery can work normally; when the temperature of the environment in which the acrylamide copolymer is located is higher than its LCST (for example, the temperature of the electrolyte rises), the acrylamide copolymer can be converted into a hydrophobic material, and then the electrolyte is discharged, the lithium ion channel is closed, the reaction of the positive and negative electrodes is cut off, and the heat of the secondary battery is prevented from further accumulating, that is, the diaphragm realizes a self-regulating thermal shutdown effect. Moreover, the hydrophilicity or hydrophobicity of the acrylamide copolymer is completely reversible at an ambient temperature lower than or higher than its LCST. Therefore, when the separator using the acrylamide copolymer is used in a secondary battery, on the one hand, a thermal shutdown effect at high temperature can be achieved. On the other hand, if the ambient temperature of the acrylamide copolymer drops below its LCST, the lithium ion channel is restored and the secondary battery can still be used normally.
[0038] According to some embodiments of the present invention, the weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is (2:8) to (8:2). Specifically, the weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is 2:8, 3:7, 4:6, 5:5, 6:4, 7:3, 8:2 or any value therebetween. According to some embodiments of the present invention, the weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is (3:7) to (7:3).
[0039] According to some embodiments of the present invention, the cross-linking agent comprises methylenebisacrylamide, the catalyst comprises ammonium persulfate, the solvent comprises deionized water, and the initiator comprises tetramethylethylenediamine.
[0040] According to some embodiments of the present invention, the weight ratio of the acrylamide monomer to the crosslinking agent is (10-50): 1. Specifically, the weight ratio of the acrylamide monomer to the crosslinking agent is 10: 1, 15: 1, 20: 1, 25: 1, 30: 1, 35: 1, 40: 1, 45: 1, 50: 1 or any value therebetween.
[0041] According to some embodiments of the present invention, the weight ratio of the acrylamide monomer to the initiator is (10-30): 1. Specifically, the weight ratio of the acrylamide monomer to the initiator is 10:1, 15:1, 20:1, 25:1, 30:1 or any value therebetween.
[0042] According to some embodiments of the present invention, the weight ratio of the acrylamide monomer to the catalyst is (10-30): 1. Specifically, the weight ratio of the acrylamide monomer to the catalyst is 10: 1, 15: 1, 20: 1, 25: 1, 30: 1 or any value therebetween.
[0043] According to some embodiments of the present invention, the drying temperature is 110°C to 130°C, and the time is 1 hour to 3 hours. Specifically, the drying temperature is 110°C, 112°C, 114°C, 116°C, 118°C, 120°C, 122°C, 124°C, 126°C, 128°C, 130°C or any value therebetween, and the time is 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours or any value therebetween.
[0044] According to some embodiments of the present invention, the weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is (3:7) to (7:3). Specifically, the weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is 3:7, 4:6, 5:5, 6:4, 7:3 or any value therebetween. According to some embodiments of the present invention, the weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is (4:6) to (6:4).
[0045] Secondary battery
[0046] The present invention also aims to provide a secondary battery, which comprises a positive electrode sheet, a negative electrode sheet, an electrolyte, and a diaphragm according to the present application or a diaphragm prepared according to the method of the present application.
[0047] The present invention obtains a diaphragm with a self-regulating thermal shutdown effect by arranging an acrylamide copolymer on the diaphragm to form a copolymer layer, thereby solving the thermal runaway problem of the secondary battery and improving the safety performance of the secondary battery without affecting the electrochemical performance.
[0048] According to some embodiments of the present invention, the electrolyte of the present invention may be an electrolyte known in the prior art. The electrolyte includes an organic solvent, a lithium salt and an optional additive. The organic solvent in the electrolyte of the present invention may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present invention is not limited and may be any electrolyte known in the prior art. The additive of the electrolyte according to the present invention may be any additive known in the prior art that can be used as an electrolyte additive.
[0049] According to some embodiments of the present invention, the first lithium salt comprises lithium nitrate (LiNO 3 ), lithium sulfate (LiSO 4 ) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), wherein the concentration of the first lithium salt is 0.8 mol / L to 1.2 mol / L. Specifically, the concentration of the lithium salt is 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L or any value therebetween. Without being bound by existing theories, the inventors of the present invention have found that the type and content of lithium salts will affect the temperature-sensitive properties of the polymer, and including LiNO 3 、LiSO 4 The chaotropic lithium salt of at least one of LiTFSI and LiO has little effect on LCST, can set more precise control on LCST, and can make the separator have good lithium ion conductivity. According to some embodiments of the present invention, the lithium salt includes lithium nitrate, thereby, can set more precise control on LCST.
[0050] In some embodiments, the electrolyte further comprises other lithium salts, including lithium hexafluorophosphate (LiPF 6 ), lithium tetrafluoroborate (LiBF 4), lithium trifluorosulfonyl (LiTf), lithium bis(fluorosulfonyl) imide (LiFSI), lithium trifluoromethanesulfonate, lithium (trifluoromethylsulfonyl) (perfluorobutylsulfonyl) imide (LiFNFSI), lithium bis(pentafluoroethylsulfonic acid) imide (LiBETI), lithium bis(fluoromalonate) borate (LiBFMB), lithium bis(oxalate borate) (LiBOB), lithium difluorooxalate borate (LiDFOB), lithium difluorobis(oxalate phosphate) and lithium 4,5-dicyano-2-(trifluoromethyl) imidazole (LiTDI). In some embodiments, the mass percentage of other lithium salts is 4% to 25% based on the mass of the electrolyte. In some embodiments, the mass percentage of other lithium salts is 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25% or any value therebetween. In some embodiments, the mass percentage of other lithium salts is 6% to 18%.
[0051] In some embodiments, the organic solvent includes at least one of a linear carbonate, a cyclic carbonate, and a carboxylic acid ester.
[0052] In some embodiments, linear carbonate includes at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate and fluorinated linear carbonate. Fluorinated linear carbonate includes fluoroethylene carbonate (FEC). In some embodiments, cyclic carbonate includes at least one of ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate. In some embodiments, carboxylate includes at least one of methyl formate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, gamma-butyrolactone and fluorinated carboxylate.
[0053] In some embodiments, the mass percentage of the solvent is 40% to 80% based on the mass of the electrolyte. In some embodiments, the mass percentage of the solvent is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any value therebetween. In some embodiments, the mass percentage of the solvent is 50% to 70%.
[0054] In some embodiments, the additive includes at least one of a cyclic carbonate containing a carbon-carbon double bond, a silyl-containing phosphate, a silyl-containing borate, a nitrile compound, and a propanesulfonic acid pyridinium salt. In some embodiments, the additive includes at least one of vinylene carbonate (VC), vinylethylene carbonate (VEC), tris(trimethylsilyl)phosphate (TMSP), tris(trimethylsilyl)borate (TMSB), succinonitrile, adiponitrile, glutaronitrile, and hexanetrinitrile. In some embodiments, the additive further includes at least one of methylene methyl disulfonate (MMDS), ethylene ethyl disulfonate, 1,3-propane sultone (PS), 1-propylene-1,3-sultone (PST), 1,4-butane sultone (1,4-BS), diethylene sulfate (DTD), 4-methylethylene sulfate (PCS), 4-ethylethylene sulfate (PES), 4-propylethylene sulfate (PEGLST), propylene sulfate (TS), ethylene sulfite (DTO), dimethyl sulfite (DMS) and diethyl sulfite (DES).
[0055] In some embodiments, the mass percentage of the additive is 0.05% to 10% based on the mass of the electrolyte. In some embodiments, the mass percentage of the additive is 0.05%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, 9%, 10% or any value therebetween. In some embodiments, the mass percentage of the additive is 0.1% to 5%.
[0056] According to some embodiments of the present invention, the operating temperature of the secondary battery is greater than the minimum eutectic temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 100° to 170°, specifically, the contact angle of the acrylamide copolymer is 100°, 110°, 120°, 130°, 140°, 150°, 160°, 170° or any value therebetween. According to some embodiments of the present invention, the operating temperature of the secondary battery is less than the minimum eutectic temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 20° to 70°, specifically, the contact angle of the acrylamide copolymer is 20°, 30°, 40°, 50°, 60°, 70° or any value therebetween. It should be noted that the operating temperature of the secondary battery is the temperature of the electrolyte in the secondary battery when the secondary battery is working. When the operating temperature of the secondary battery is lower than the lowest eutectic temperature of the acrylamide copolymer, the contact angle of the acrylamide copolymer is 20° to 70°, that is, when the temperature of the environment in which the acrylamide copolymer is located (for example, the diaphragm is located in the electrolyte, corresponding to the temperature of the electrolyte) is lower than its LCST, the acrylamide copolymer is hydrophilic, and the contact angle of the acrylamide copolymer is 20° to 70°, and for the swelling of the electrolyte, the lithium ions in the electrolyte can be freely transmitted through the diaphragm, and the secondary battery can work normally. When the operating temperature of the secondary battery is higher than the lowest eutectic temperature of the acrylamide copolymer, that is, when the temperature of the environment in which the acrylamide copolymer is located is higher than its LCST (for example, the temperature of the electrolyte rises), the acrylamide copolymer can be converted into a hydrophobic material, and the contact angle of the acrylamide copolymer is 100° to 170°, thereby discharging the electrolyte, closing the lithium ion channel, cutting off the reaction of the positive and negative electrodes, and preventing the further accumulation of heat in the secondary battery, that is, the diaphragm realizes a self-regulating thermal shutdown effect. Moreover, the hydrophilicity or hydrophobicity of the acrylamide copolymer is completely reversible at an ambient temperature lower than or higher than its LCST. Therefore, when the separator using the acrylamide copolymer is used in a secondary battery, on the one hand, a thermal shutdown effect at high temperature can be achieved. On the other hand, if the ambient temperature of the acrylamide copolymer drops below its LCST, the lithium ion channel is restored and the secondary battery can still be used normally.
[0057] According to some embodiments of the present invention, when the temperature of the acrylamide copolymer is higher than the lowest eutectic temperature, the acrylamide copolymer is hydrophobic; when the temperature of the acrylamide copolymer is lower than the lowest eutectic temperature, the acrylamide copolymer is hydrophilic, for example, in a hydrogel state. Thus, the separator according to the present invention has good lithium ion conductivity, and will not have a negative impact on the electrochemical performance of the battery while maintaining a sensitive thermal shutdown effect and improving the overall safety performance of the battery.
[0058] According to the copolymer layer of the present invention, the separator of the secondary battery not only has good ion conductivity, but also can achieve a thermal shutdown effect through the phase change performance of the copolymer layer, thereby realizing reversible intelligent regulation.
[0059] In some embodiments, the secondary battery can be any device that generates an electrochemical reaction, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the secondary battery is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, and a lithium ion polymer secondary battery.
[0060] In some embodiments, the negative electrode sheet includes a negative current collector and a negative active material layer including a negative active material, and the positive electrode sheet includes a positive current collector and a positive active material layer including a positive active material.
[0061] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, etc.) on a polymer substrate.
[0062] In some embodiments, the positive electrode active material includes a lithium nickel transition metal oxide, and the lithium nickel transition metal oxide includes LiNi x Co y M (1-x-y) O 2 At least one of the following, M includes at least one of manganese, iron, chromium, titanium, zinc, vanadium, aluminum, zirconium, cerium, magnesium, calcium, molybdenum, strontium, tungsten, copper, yttrium, lanthanum, gallium, silver and niobium, 0.5≤x≤1, 0≤y≤0.5, x+y≤1.
[0063] In some embodiments, x is 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, 1, or any value therebetween. In some embodiments, y is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or any value therebetween.
[0064] In some embodiments, the positive electrode active material includes at least one of lithium nickel oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese cobalt magnesium oxide, and lithium nickel manganese oxide. In some embodiments, the positive electrode active material includes at least one of NCA, NCM111, NCM523, NCM622, NCM811, Ni90, Ni92, and Ni95.
[0065] In some embodiments, the positive electrode active material includes a phosphate, and the phosphate includes LiMn k B (1-k) PO 4 At least one of, wherein 0≤k≤1, the B element comprises at least one of iron, cobalt, magnesium, calcium, zinc, chromium and lead. In some embodiments, k is 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95 or any value therebetween. In some embodiments, the phosphate comprises at least one of lithium iron phosphate and lithium manganese iron phosphate. In some embodiments, the phosphate comprises LiMn 0.6 Fe 0.4 PO 4 and LiMn 0.8 Fe 0.2 PO 4 At least one of .
[0066] In some embodiments, the positive electrode active material layer further includes a binder, which includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector.
[0067] In some embodiments, the positive electrode active material layer further includes a conductive agent, which includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0068] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector, such as copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or any combination thereof.
[0069] In some embodiments, the negative electrode active material includes at least one of a silicon-based material, a carbon-based material, a tin-based material, a phosphorus-based material, and metallic lithium.
[0070] In some embodiments, the silicon-based material includes at least one of silicon, silicon alloys, silicon oxides, and silicon carbon compounds. In some embodiments, the carbon-based material includes at least one of graphite, soft carbon, hard carbon, carbon nanotubes, and graphene. In some embodiments, the tin-based material includes at least one of tin, tin oxide, and tin alloys. In some embodiments, the phosphorus-based material includes phosphorus and / or phosphorus compounds.
[0071] In some embodiments, based on the mass of the negative electrode active material, the mass percentage z% of the silicon-based material satisfies: 10≤z≤100. In some embodiments, z is 10, 11, 13, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 or any value therebetween.
[0072] In some embodiments, the negative electrode active material layer also includes a binder, which includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0073] In some embodiments, the negative electrode active material layer further includes a conductive agent, which includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, and a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0074] Device
[0075] The present invention further provides a device comprising the secondary battery of the present invention.
[0076] The electronic device or device of the present invention is not particularly limited. In some embodiments, the electronic device of the present invention includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car (electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle), a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc.
[0077] Examples and Comparative Examples
[0078] Example 1
[0079] Preparation of acrylamide copolymer:
[0080] 3 g of acrylamide monomer, 7 g of N-isopropylacrylamide monomer, 0.1 g of methylenebisacrylamide and 0.2 g of ammonium persulfate were added to 40 ml of deionized water, stirred evenly in an ice-water bath, and argon or nitrogen was introduced into the solution to deoxygenate;
[0081] 0.2 g of tetramethylethylenediamine (TEMED initiator) was added to the solution and stirred, and reacted for 30 seconds to obtain an acrylamide copolymer.
[0082] Diaphragm coating:
[0083] The acrylamide copolymer was coated on both sides of a base film (polyethylene PE base film, 12 μm thick) by roller coating, with a single-side copolymer layer thickness of 5 μm. The diaphragm was then placed in an oven at 120°C and dried for 2 hours to obtain a diaphragm having a copolymer layer.
[0084] Positive electrode preparation:
[0085] The ternary material (NCM811), the conductive agent carbon black SP, and polytetrafluoroethylene (PVDF) are dispersed in N-methylpyrrolidone (NMP) at a weight ratio of 96:3:1, and the mixture is stirred and mixed to obtain a positive electrode slurry. The positive electrode slurry is coated on an Al foil current collector with a thickness of 10 μm. Both surfaces of the Al foil current collector are provided with a conductive carbon layer with a thickness of 1 μm. The Al foil current collector with a conductive carbon layer has a thickness of 12 μm. The coated positive electrode current collector is dried in a vacuum oven at 110°C for 9 hours, and the positive electrode sheet is obtained after rolling and die-cutting.
[0086] Negative electrode sheet preparation:
[0087] Sodium carboxymethyl cellulose (CMC) is dispersed in deionized water and stirred evenly to obtain CMC glue. Then, graphite material, conductive carbon black, binder (styrene-butadiene rubber) and sodium carboxymethyl cellulose glue are mixed evenly in a mass ratio of 96.0:1.0:2:1 to obtain negative electrode slurry. The negative electrode slurry is coated on both sides of copper foil, and after drying, calendering and vacuum drying, a negative electrode sheet is obtained.
[0088] Preparation of electrolyte:
[0089] Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1, and then LiNO 3 , and mix well to obtain an electrolyte. 3 The content is 1mol / L.
[0090] Soft pack battery assembly:
[0091] The above-mentioned separator with a copolymer layer is placed between the positive electrode sheet and the negative electrode sheet, and a sandwich structure consisting of 11 positive electrode sheets, the separator and 12 negative electrode sheets is stacked, and then placed in an aluminum-plastic film packaging bag. After vacuum baking at 75°C for 48 hours, the electrolyte is injected into the battery cell, and a lithium-ion soft-pack battery is obtained after vacuum packaging, aging, formation and capacity separation.
[0092] Example 2
[0093] Example 2 was carried out by substantially the same method as Example 1, except that, in coating the separator, the acrylamide copolymer was coated only on one side of the separator.
[0094] Example 3
[0095] Example 3 was carried out by substantially the same method as Example 1, except that in the preparation of the acrylamide copolymer, the amount of acrylamide used was 5 g, and the amount of N-isopropylacrylamide used was 5 g.
[0096] Example 4
[0097] Example 4 was carried out by substantially the same method as Example 1, except that the coating of the separator was carried out as follows:
[0098] The acrylamide copolymer in the form of a hydrogel is coated on both sides of the base film (PE base film, thickness of 12 μm) by roller coating, and the thickness of the copolymer layer on one side is 10 μm. Then the membrane is placed in an oven at 120°C and dried for 2 hours to obtain a membrane with a copolymer layer.
[0099] Example 5
[0100] Example 5 was carried out by substantially the same method as Example 1, except that in the preparation of the acrylamide copolymer, the amount of acrylamide used was 4 g, and the amount of N-isopropylacrylamide used was 6 g.
[0101] Example 6
[0102] Example 6 was carried out by substantially the same method as Example 1, except that in the preparation of the acrylamide copolymer, the amount of acrylamide used was 2 g, and the amount of N-isopropylacrylamide used was 8 g.
[0103] Example 7
[0104] Example 6 was carried out by substantially the same method as Example 1, except that in the preparation of the acrylamide copolymer, the amount of acrylamide used was 7 g, and the amount of N-isopropylacrylamide used was 3 g.
[0105] Example 8
[0106] Example 6 was carried out by substantially the same method as Example 1, except that in the preparation of the acrylamide copolymer, the amount of acrylamide used was 8 g, and the amount of N-isopropylacrylamide used was 2 g.
[0107] Comparative Example 1
[0108] Comparative Example 1 was carried out by substantially the same method as Example 1, except that, in the preparation of the acrylamide copolymer, the amount of acrylamide used was 9 g, and the amount of N-isopropylacrylamide used was 1 g.
[0109] Comparative Example 2
[0110] Comparative Example 2 was prepared by substantially the same method as Example 1, except that, in the preparation of the acrylamide copolymer, the amount of acrylamide used was 1 g, and the amount of N-isopropylacrylamide used was 9 g.
[0111] Comparative Example 3
[0112] Comparative Example 3 was carried out by substantially the same method as Example 1, except that a commercially available polyethylene PE-based film having a thickness of 12 μm was provided as a separator.
[0113] Test method
[0114] 1. Minimum eutectic temperature (LCST) test
[0115] The DSC instrument was used for testing, and the test atmosphere was N 2 The gas was heated at a rate of 10°C / min from -40°C to 200°C, and the peak position of the phase change peak between 0 and 100°C was taken as the LCST.
[0116] 2. Hot box passing temperature
[0117] At 25°C, charge at a constant current of 0.5C until the charge termination voltage is reached, then switch to constant voltage charging until the charge current rate drops to 0.05C, stop charging, and let stand for 30 minutes;
[0118] Put the battery into the test box. The test box is heated at a rate of 5℃ / min. When the temperature inside the box reaches 120℃±2℃, keep the temperature constant. If the battery does not smoke, catch fire or explode for 1 hour, it is considered to have passed. Otherwise, it is considered to have failed.
[0119] Carry out the temperature increase experiment in steps of 5°C and record the highest temperature that the battery passes as the hot box temperature.
[0120] 3. Contact angle test
[0121] Drop a liquid drop on the surface of a solid sample, obtain an image of the drop's appearance through a microscope lens and a camera, and calculate the contact angle using digital image processing software (for example, using the Young-Laplace equation to calculate the contact angle of the drop in the image).
[0122] Table 1
[0123]
[0124] "NA" means not present.
[0125] As can be seen from Table 1, by comparing Examples 1 and 2, it is found that double-sided coating can obtain a higher hot box pass temperature than single-sided coating. Although the diaphragm in Example 8 was slightly cracked, the desired hot box pass temperature was still obtained, thereby improving the safety performance of the battery. However, in Comparative Example 1, due to the excessive content of acrylamide monomer when preparing the acrylamide copolymer, the diaphragm cracked, affecting the assembly and processing performance of the battery. In Comparative Example 2, due to the excessive content of N-isopropylacrylamide monomer when preparing the acrylamide copolymer, the hot box pass temperature was low, indicating that the battery has thermal runaway at this temperature and the safety performance is poor. In Comparative Example 3, since the copolymer layer containing acrylamide copolymer is not provided in the diaphragm, the diaphragm cannot achieve a self-regulating thermal shutdown effect, and the hot box pass temperature is low, indicating that the battery has thermal runaway at this temperature and the safety performance is poor.
[0126] Although some exemplary embodiments of the present invention have been illustrated and described, the present invention is not limited to the disclosed embodiments. On the contrary, those of ordinary skill in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present invention as described in the appended claims, and these modifications and changes also fall within the scope of protection of the present invention.
Claims
1. A diaphragm, characterized in that: include: Basement membrane; A copolymer layer, the copolymer layer is disposed on the base film, the copolymer layer comprises an acrylamide copolymer, the acrylamide copolymer comprises a first unit as shown in Formula I and a second unit as shown in Formula II: Wherein, based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 16% to 96%, and the mass percentage of the second unit is 4% to 84%.
2. The diaphragm according to claim 1, characterized in that The acrylamide copolymer satisfies at least one of the following conditions: (1) The acrylamide copolymer includes: a copolymer obtained by copolymerization of acrylamide monomer and N-isopropylacrylamide monomer; (2) In the acrylamide copolymer, the arrangement of the first unit and the second unit includes at least one of a random copolymerization arrangement, an alternating copolymerization arrangement, a block copolymerization arrangement and a graft copolymerization arrangement.
3. The diaphragm according to claim 1, characterized in that The acrylamide copolymer satisfies at least one of the following conditions: (3) Based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 28% to 94%, and the mass percentage of the second unit is 6% to 72%; (4) The weight average molecular weight of the acrylamide copolymer is 200,000 Da to 2,000,000 Da; (5) The thickness of the copolymer layer is 1 μm to 10 μm; (6) The minimum solubility temperature of the acrylamide copolymer is 50°C to 110°C.
4. The diaphragm according to claim 3, characterized in that The diaphragm satisfies at least one of the following conditions: (7) The base film comprises at least one of polyethylene, polypropylene, polypropylene / polyethylene / polypropylene three-layer film, polyethylene terephthalate, polyimide and aramid; (8) The thickness of the base film is 2 μm to 12 μm; (9) The copolymer layer is disposed on the surfaces of opposite sides of the base film; (10) Based on the mass of the acrylamide copolymer, the mass percentage of the first unit is 40% to 80%, and the mass percentage of the second unit is 20% to 60%; (11) The weight average molecular weight of the acrylamide copolymer is 300,000 Da to 800,000 Da; (12) The thickness of the copolymer layer is 2 μm to 5 μm; (13) The minimum solubility temperature of the acrylamide copolymer is 55°C to 85°C.
5. The diaphragm according to claim 4, characterized in that The diaphragm satisfies at least one of the following conditions: (14) The temperature of the environment in which the acrylamide copolymer is located is greater than the minimum solubility temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 100° to 170°; (15) The temperature of the environment in which the acrylamide copolymer is located is lower than the minimum solubility temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 20° to 70°.
6. A method for preparing a diaphragm, characterized in that: include: Mixing acrylamide monomer, N-isopropylacrylamide monomer, crosslinking agent, catalyst and solvent to obtain a first mixture; adding an initiator to the first mixture, and obtaining a second mixture containing an acrylamide copolymer through reaction treatment; The second mixture is coated on a base film, and the separator is obtained through a drying process.
7. The preparation method according to claim 6, characterized in that: The preparation method satisfies at least one of the following conditions: (16) The weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is (2:8) to (8:2); (17) The cross-linking agent includes methylenebisacrylamide, the catalyst includes ammonium persulfate, the solvent includes deionized water, and the initiator includes tetramethylethylenediamine; (18) The drying process is performed at a temperature of 110° C. to 130° C. and for a time of 1 hour to 3 hours.
8. The preparation method according to claim 7, characterized in that: The weight ratio of the acrylamide monomer to the N-isopropylacrylamide monomer is (3:7) to (7:3).
9. A secondary battery, characterized in that: include: A positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator according to any one of claims 1 to 5 or a separator prepared by the preparation method according to any one of claims 6 to 8.
10. A secondary battery according to claim 9, characterized in that: The secondary battery satisfies at least one of the following conditions: (19) The electrolyte includes a first lithium salt, the first lithium salt includes at least one of lithium nitrate, lithium sulfate and lithium bis(trifluoromethanesulfonyl)imide, and the concentration of the first lithium salt is 0.8 mol / L to 1.2 mol / L; (20) The operating temperature of the secondary battery is greater than the minimum solubility temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 100° to 170°; (21) The operating temperature of the secondary battery is lower than the minimum solubility temperature of the acrylamide copolymer, and the contact angle of the acrylamide copolymer is 20° to 70°.